#TITLE_ALTERNATIVE# - DAVID DANIEL (NIM 13203124), FINLEY
The unmanned aerial vehicle (UAV) technology has been attracts the interest of many researchers around the world in the past decades. By definition, UAV is a small size aerial vehicle that controlled by remote control device or automatically controls itself to complete certain mission without outside intervention. Considering the lack of research on this field and the huge potentials use of UAV in Indonesia, which has vast territory and various natural contours, we hoped that this research will be a stepping stone for UAV development in Indonesia. On this Final Project, rotary wing is the UAV's type being used. The platform is the X-Cell 60 SE helicopter. The first step will be developing a linear model. The model is being developed using prediction error minimization (PEM) based system identification. This method will be combined with the first-principle method that has been developed by Budiyono, 2007 [2] to increase its accuracy. The linear model being developed is limited on cruise flying mode. After done with the model, next step is designing the control system. The control systems being developed are altitude hold system and heading hold system. In designing the control systems, PID controller with the cascade structure is chosen. The control systems will be implemented using microcontroller. Then, the whole system will be tested using hardware-in-the-loop simulation (HILS). The HILS will be implemented using Matlab R2007a, Simulink and X-Plane v8.21 for the visualization interface. It is demonstrated that the proposed technique can enhance the accuracy of dynamics model obtained from the first-principle prediction. It also demonstrated that the altitude and heading hold system performance is better by using cascade PID structure. Also by using HILS, the efficiency in designing and testing the control system algorithm can be increased.